Сутність і функціональні можливості Revenue-менеджменту: історичний контекст - Чайка, Тетяна Юріївна (Видавничий дім "Гельветика", 2025)
Метою статті є вивчення історично сформованих умов, під впливом яких складалися функціональні можливості Revenue-менеджменту; уточнення та систематизація базових характеристик тих галузей економіки, для яких застосування Revenue-менеджменту здатне дати найбільший ефект. Дослідження показало, що історично бізнес-стратегія Revenue-менеджменту виникла у США в період 1976–1983 рр. як реакція на проблемну ситуацію низького обсягу продажів квитків на авіарейси в умовах відсутності цінової дискримінації. Основною причиною існування проблемної ситуації було жорстке державне регулювання авіаперевезень. А сама можливість виникнення Revenue-менеджменту з'явилася внаслідок подальшого ска- сування жорсткого державного регулювання. У результаті еволюційного розвитку Revenue-менеджменту з'явився інструмент, націлений на роботу з бізнес-напрямками, для яких характерні: «швидкопсувний» ха- рактер товару (послуги); порівняно низькі змінні витрати; можливість сегментації попиту; можливість диференціації послуг за різними критеріями. The paper focuses on the study of the historical context of the emergence of Revenue Management business strategy. The influence of Revenue Management development drivers on the formation of its specific tools and functionalities is studied. The relevance of this paper is due to the need to clarify the functionality of Revenue Management strategy and to identify the basic characteristics of a limited number of industries for which the application of Revenue Management can give the greatest effect. The purpose of the paper is to examine the historical conditions under the influence of which the functionality of Revenue Management was formed; to clarify and systematize the characteristic features of such types of economic activities, for which the application of Revenue Management strategy allows to obtain the maximum effect. The following methods were used in the study: comparative analysis (when working with primary sources of information about the emergence and development of Revenue Management); logical-analytical and system-structural methods (when studying the formation and development of tools and functionality of Revenue Management). The research has shown that historically the business strategy of Revenue Management emerged in the USA in the period 1976–1983 as a reaction to the problematic situation of low sales of airline tickets in the absence of price discrimination. The main reason for the existence of the problematic situation was the strict state regulation of air travel. The possibility of Revenue Management emerged due to the cancellation of strict state regulation. The formation of functional capabilities of Revenue Management directly depends on what problem situations and in what industries were solved with the help of Revenue Management throughout the history of its development. As a result, a tool aimed at working with business areas characterised by: the ‘perishable’ nature of goods; relatively low variable costs; the possibility of segmenting demand; and the possibility of differentiating services according to various criteria. Accordingly, when making a decision on the use of Revenue Management business strategy in the activities of a particular company, it is necessary to take into account the correspondence of the basic characteristics of this company to the basic characteristics of those industries in which Revenue Management shows the greatest efficiency.
The essence and functionality of Revenue management: historical context
Keywords: Revenue-менеджмент; цінова дискримінація; цінова політика; поведінкові переваги клієнтів; сегментація споживачів; Revenue Management; price discrimination; pricing policy; customer behavioural preferences; customer segmentation